Experimental, numerical and analytical investigations of masonry corners: Influence of the horizontal pseudo-static load orientation - Colombo, Carla (2022)
Colombo, Carla, Funari, Marco Francesco, Savalle, Nathanaël, & Lourenço, Paulo B. (2021). Tilting test campaign on masonry corners (2021-06-03, UMinho) [Data set]. Zenodo. https://doi.org/10.5281/zenodo.5572624